Injury profile among elite male youth soccer players in a Swedish first league - Nilsson, T.; Hafsteinsson Östenberg, A.; Alricsson, M. (Journal of Exercise Rehabilitation, 2016)
This study investigated the injury profile among elite male youth soccer players in a Swedish first league during two seasons. The present cohort study is based on data collected during the 2013-2014 seasons. In total, 43 young elite male soccer players, aged 15 to 19 yr, were prospectively followed regarding injuries, time of exposure, injury location, type of injury, and injury severity. The overall incidence of injury in the present study was estimated to 6.8 injuries per 1,000 exposure hours and 15.5 and 5.6 injuries per 1,000 hr for matches and training, respectively. The single most common injury subtype was muscle strain (53%). The hip and groin were the most common locations for injuries. Thirty-one percent of the injuries were classified as severe injury and caused >28 days absence from training and match play. Both the injury incidence and the number of serious injury seems to be relatively high in youth elite players according to this study. Although the injury incidence seems to be slightly lower than in adult elite players the injuries seem to be more traumatic in youth elite players.